The Execution of Illegal Orders and International Criminal Responsibility - Sato, Hiromi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The legal consequence of the superior orders defense has long been debated as one of the major problems in international criminal law. Several controversial issues such as the immunity of the state, the absolute character of military discipline, and immunity on the grounds of mistake of law and/or coercion have been complexly interwoven in the debates. The Execution of Illegal Orders and International Criminal Responsibility provides a comprehensive portrait of the relevant debates at the international level up to the present, analyzes the conflicting views, and shows the significance of the development of international rules for the superior orders defense as well as the implication of the fact that issues concerning some detailed or related rules have been left unresolved. This study presents to present a new standpoint not only on dealing with the problem of the superior orders defense but also on reconsidering the international stipulation of rulemaking with regard to criminal matters.
1 Introduction -- 2 Before the Adoption of the Nuremberg Charter -- 3 Formation of the "Nurember Principle" -- 4 After the Trials under the Nuremberg Charter -- 5 Change of the Structural of International Legal Order and "Hesitation" -- Referenes -- Index.
Keywords: Law; Criminal Law; Comparative law; Public law; Law; European Law/Public International Law; International & Foreign Law/Comparative Law; Criminal Law